(untitled) (LIS TODAY, 2023)
The digital era has brought about a revolutionary transformation in the field of education, particularly in India, where various online platforms have emerged to supplement traditional learning methods. This paper presents a comprehensive comparative analysis of four prominent digital learning platforms in India: NPTEL (National Programme on Technology Enhanced Learning), NDL (National Digital Library), SWAYAM (Study Webs of Active-Learning for Young Aspiring Minds), and e-PG Pathshala. The study aims to evaluate their impact, effectiveness, and contribution to India’s educational landscape. This study compares four major digital learning platforms in India – NPTEL, NDL, SWAYAM, and e-PG Pathshala – to assess their impact on education. Examining aspects like content diversity, accessibility, and user satisfaction, we find NPTEL excels in tech education, NDL is a comprehensive digital library, SWAYAM promotes interactive learning, and e-PG Pathshala focuses on postgraduate education. Challenges like internet connectivity and digital literacy are noted. Recommendations include increased collaboration and enhanced user support. This analysis informs policymakers and educators navigating the evolving landscape of digital education in India. This comparative study will provide valuable insights for educators, policymakers, and e-learning platform developers in India. It will help them understand the strengths and weaknesses of these platforms, allowing for informed decisions on how to enhance the learning experiences of students across the country. Additionally, the study may contribute to the broader discourse on the role of e-learning in shaping the future of education in India.